An Acute Multispecies Episode of Sheep‐Associated Malignant Catarrhal Fever in Captive Wild Animals in an Italian Zoo. Issue 6 (19th January 2015) - Frontoso, R.; Autorino, G. L.; Friedrich, K. G.; Li, H.; Eleni, C.; Cocumelli, C.; Di Cerbo, P.; Manna, G.; Scicluna, M. T.
Summary: In July 2011, in a zoological garden in Rome, Italy, malignant catarrhal fever (MCF), a fatal, systemic disease of Artiodactyla, was suspected on the basis of neurological signs and gross lesions observed in a banteng, the first animal to die of this infection. An MCF type‐specific PCR with subsequent sequencing of the PCR amplicon confirmed the aetiological agent as ovine herpesvirus‐2 (OvHV‐2). Biological samples were collected from the dead animals for gross, histological, bacteriological, virological and serological examinations. An epidemiological investigation was conducted to identify the source of the outbreak, as further deaths due to OvHV‐2 still occurred after the removal of the acknowledged reservoirs, domestic sheep and goats. For this purpose, samples from other susceptible species and reservoir hosts were collected for virological and serological analysis. In conjunction, a retrospective sero‐investigation was conducted on sera collected between 1999 and 2010 from some of the species involved in the present episode. In total, 11 animals belonging to four different species (banteng, Himalayan tahr, Nile lechwe and sika deer) died between July 2011 and October 2012. The severe gross and histological lesions were consistent with the disease, namely haemorrhages and congestion of several organs as well as lymphoid cell infiltrates and vasculitis of varying severity. The virological tests confirmed that all animals had died of sheep‐associated MCF. The investigation indicated that the OvHV‐2 infection could have been due to the arrival of sheep in the petting zoo, with cases commencing after first lambing and subsequent shedding of virus. This was also supported by the serological retrospective study that indicated limited previous MCF virus circulation. Further MCF cases that occurred even after the removal of the domestic sheep and goats were attributed to the mouflon. This episode confirms the importance of biosecurity measures in zoos, which house MCF susceptible species, especially those endangered.